Reflections on Competency Based Assessment in Education - Arturo De la Orden Hoz (Universidad Autónoma de Baja California, 2011)
Ensuring a positive impact of assessment on Competency Based Education (CBE) requires, obviously, an educationally valid assessment system. It is therefore necessary that competency be specified and defined as an object of assessment. Following a review of the relevant literature, this article presents two conceptions of competency: 1) Competency as effective and efficient performance of a function or role in a given area, and 2) Competency as an integrated combination of knowledge, abilities, skills and attitudes. The first conception of competency calls for a more holistic evaluation model, which is to say a comprehensive appraisal of competency, rather than an analytical assessment of its requirements. With regard to the second conception of competency, a theoretically adequate model is the one known as Performance Assessment. The article concludes with a reference to advanced models of performance assessment and to their design structure, closing with a brief allusion to the validation of competency assessment systems.